Synchronized dynamics of bacterial niche‐specific functions during biofilm development in a cold seep brine pool. (17th August 2015) - Zhang, Weipeng; Wang, Yong; Bougouffa, Salim; Tian, Renmao; Cao, Huiluo; Li, Yongxin; Cai, Lin; Wong, Yue Him; Zhang, Gen; Zhou, Guowei; Zhang, Xixiang; Bajic, Vladimir B.; et al.
Summary: The biology of biofilm in deep‐sea environments is barely being explored. Here, biofilms were developed at the brine pool (characterized by limited carbon sources) and the normal bottom water adjacent to Thuwal cold seeps. Comparative metagenomics based on 50 Gb datasets identified polysaccharide degradation, nitrate reduction and proteolysis as enriched functional categories for brine biofilms. The genomes of two dominant species: a novel Deltaproteobacterium and a novel Epsilonproteobacterium in the brine biofilms were reconstructed. Despite rather small genome sizes, the Deltaproteobacterium possessed enhanced polysaccharide fermentation pathways, whereas the Epsilonproteobacterium was a versatile nitrogen reactor possessing nar, nap and nif gene clusters. These metabolic functions, together with specific regulatory and hypersaline‐tolerant genes, made the two bacteria unique compared with their close relatives, including those from hydrothermal vents. Moreover, these functions were regulated by biofilm development, as both the abundance and the expression level of key functional genes were higher in later stage biofilms, and co‐occurrences between the two dominant bacteria were demonstrated. Collectively, unique mechanisms were revealed: (i) polysaccharides fermentation, proteolysis interacted with nitrogen cycling to form a complex chain for energy generation, and (ii) remarkably exploiting and organizing niche‐specific functions would be an important strategy for biofilm‐dependent adaptation to the extreme conditions.